Evaluation of clinical results and complications of internal fixation of intertrochanteric femur fracture with proximal femoral nail antirotation - Raj, Manish; Gill, S. P. S.; Singh, Akashdeep; Rajput, Ajay Kumar; Singh, Santosh Kumar (International Journal of Research in Orthopaedics, 2019)
Background: The purpose of the present study was to evaluate the theoretical advantages of the proximal femoral nail antirotation in cases of intertrochanteric fractures and also whether it actually alters the eventual functional outcome of the patient. Methods: The present study includes a total 30 patients with intertrochanteric femur fractures managed with proximal femoral nail antirotation between December 2014 to November 2016. In all patients similar standard physical rehabilitation therapy were followed. All complications including intra and postoperative were assessed and recorded. The patients were followed up for over 24 months. Functional outcome was assessed using the Harris hip score. Results: All of 30 cases of intertrochanteric fracture got united with good anatomical position and average time of fracture union was 14 weeks. Postoperative complications included 2 degree varus deformity (n=1, 3%), calcification at tip of greater trochanter (n=4, 13%), sensitivity over TFL (n=2, 7%), medial thigh pain (n=3, 10%). 10 patients developed femoral shortness (mean=0.22 cm, range from 0-1 cm). Average harris hip score at the end of study showed mean value of 87, ranged from 65 to 94 with almost 22 (73%) patients showing excellent or good outcome. Conclusions: Proximal femoral nail antirotation (PFNA) represents a significant treatment option in management of intertrochanteric fractures with low complication rate.